The Effect of Active Learning on Accountancy Student Learning Satisfaction through Learning Styles As Moderating Variable - Ma’ruf Nuris, Dudung; ., Sunaryanto; Minerva Nagari, Primasa (KnE Social Sciences, 2020)
In active learning, students engaged in several activities that can stimulate them to think and interact with the information presented, so as to create their own understanding and information through reflection. Students who are able to understand learning well will be satisfied with the learning process that occurs. Learning satisfaction can be determined by the teaching and learning process conducted by lecturers, but it can also be seen from the behavior of students in receiving learning in class. This study aims to determine the effect of active learning on student satisfaction with learning style as a moderating variable. This type of research used in quantitative explanatory research using path analysis. 73 students of accounting education courses in 2016 were examined in this study. In this study, the sample was taken by using a random sampling technique. Based on the results of the study indicate that there is a direct effect of active learning variables on student satisfaction and there is an indirect effect of active learning variables on student learning decisions through learning styles. This means that the influence of learning styles possessed by students is able to determine the amount of student learning satisfaction in class. Keywords: Active Learning, Learning Satisfaction, Learning Style